Consensus guidelines for the use of bowel preparation prior to colonic diagnostic procedures: colonoscopy and small bowel video capsule endoscopy. (3rd June 2013) - Mathus-Vliegen, Elisabeth; Pellisé, Maria; Heresbach, Denis; Fischbach, Wolfgang; Dixon, Tricia; Belsey, Jonathan; Parente, Fabrizio; Rio-Tinto, Ricardo; Brown, Alistair; Toth, Ervin; Crosta, Cristiano; Layer, Peter; et al.
Abstract: Background: Adequate bowel preparation prior to colonic diagnostic procedures is essential to ensure adequate visualisation. Scope: This consensus aims to provide guidance as to the appropriate use of bowel preparation for a range of defined clinical circumstances. A consensus group from across Europe was convened and met to discuss appropriate bowel preparation. The use of polyethylene glycol (PEG), sodium picosulphate and sodium phosphate (NaP), together with other agents, prokinetics and simethicone, in colonoscopy and small bowel video capsule endoscopy were considered. A systematic review of the literature was carried out and additional unpublished data was obtained from the members of the consensus group where required. Recommendations were graded according to the level of evidence. Findings: PEG-based regimens are recommended first line for both procedures, since their use is supported by good efficacy and safety data. Sodium-picosulphate-based regimens are recommended second line as their cleansing efficacy appears less than PEG-based regimens. NaP is not recommended for bowel cleansing due to the potential for renal damage and other adverse events. However, the use of NaP is acceptable in patients in whom PEG or sodium picosulphate is ineffective or not tolerated. NaP should not be used in patients with chronic kidney disease, pre-existing electrolyte disturbances, congestive heart failure, cirrhosis or a history of hypertension. The timing of the dose, dietary restrictions, use in special patient groups and recording of the quality of bowel preparation are also considered for patients undergoing colonoscopy. During the development of the guidelines the European Society of Gastrointestinal Endoscopy (ESGE) issued guidance on bowel preparation for colonoscopy. The ESGE guidelines and these consensus guidelines share many recommendations; differences between the guidelines are reviewed. Conclusion: The use of bowel preparation should be tailored to the individual patient and their specific clinical circumstances.